Radiation characterisation and dosimetric measurements of a femtosecond pulsed laser ablation system. (8th May 2018) - Prieto-Pena, J; Gómez, F; González-Castaño, D M; Flores-Arias, M T; Arines, J; Bao-Varela, C; Cambronero-López, F; Maqueira, A Martínez
Abstract: This work describes the radiation characterisation and dosimetric measurements performed on the low-energy micromachining station of the femtosecond STELA (Santiago TErawatt LAser) at the University of Santiago de Compostela (Spain). For this aim, ionisation chambers, solid state detectors, and radiochromic films were used. The results show the emission of pulsed x-ray produced by laser-accelerated electrons from the ablated material exhibiting both bremsstrahlung and characteristic radiation. Although this radiation was produced unintentionally, a high superficial dose rate can be achieved. This radiation can be successfully stopped using small shielding to protect personnel from its effects. Based on the results of this work, the yearly dose equivalent after installing the shielding was negligible.